2011
DOI: 10.5550/sgia.110701.en.017p
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Adaptive Processes of Kinematic and Dynamic Performances of Running at Maximum Speed in Training With Additional Inertial Load Application

Abstract: SUMMARYPrediction of final race time in slalom based on the time achieved in first and second race is a paper with a purpose and a primary goal to address the attention to relevant factors that determine final result in alpine skiing, and all that based on exact indicators gained under exact and strictly con� trolled rules of FIS. The mentioned example is about slalom discipline. Due to the fact that the result is a primary goal, the asked question is: Does the final result depend more on time achieved in firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A six week training study utilising 5% BM ankle WR was found to elicit a significant increase in stride length (5.3%, ES = 0.43) and decrease in stride frequency (−5.6%, ES = 0.54) as measured between 25 and 50 m with no significant changes to maximal running speed (Pajic et al., 2011). Furthermore, this training was found to have significantly increased all angles measured (knee angle at take‐off, knee angle at contact, knee flexion during backswing, and elbow flexion during backswing) suggesting a more upright body posture.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A six week training study utilising 5% BM ankle WR was found to elicit a significant increase in stride length (5.3%, ES = 0.43) and decrease in stride frequency (−5.6%, ES = 0.54) as measured between 25 and 50 m with no significant changes to maximal running speed (Pajic et al., 2011). Furthermore, this training was found to have significantly increased all angles measured (knee angle at take‐off, knee angle at contact, knee flexion during backswing, and elbow flexion during backswing) suggesting a more upright body posture.…”
Section: Resultsmentioning
confidence: 99%
“…Only one longitudinal study has investigated the effects of lower limb WR training on sprint performance. It was observed that 5% BM ankle WR elicited a significant increase in stride length (5.3%, ES = 0.43) and decrease in stride frequency (−5.6%, ES = 0.54) with non‐significant changes (ES = 0.12) to maximal running speed (Pajic et al., 2011). While increases in running speed over time have been shown to coincide with an increase in step length and is believed to be important for development of maximal speed sprinting (Nagahara & Zushi, 2017) the accompanying decrease in stride frequency seen in Pajic et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations